RCTV Cirebon’s Social Media Specialist’s Strategy for Countering Misinformation on Instagram - Fatimah Azzahra; Khaerudin Imawan (CONVERSE Journal Communication Science, 2026)
The rapid and participatory development of social media as a digital communication space has increased the risk of misinformation dissemination within society. In this context, media institutions are required not only to function as information distributors but also as gatekeepers responsible for maintaining accuracy, validity, and credibility in the digital sphere. This study aims to analyze the strategies implemented by the Social media specialist of RCTV Cirebon in countering misinformation on Instagram and to examine how these strategies contribute to strengthening public trust, particularly within the local community. The research employs a descriptive qualitative approach, utilizing in-depth interviews, observation, and documentation as data collection techniques. The informants consist of the Deputy Director and the social media management team of RCTV Cirebon. The findings indicate that the strategies include controlled management of audience participation, the implementation of multi-layered verification processes prior to publication, and consistency in maintaining the account’s identity as an official and credible source of information. These strategies demonstrate the role of the Social media specialist as a bridge between professional journalistic practices and the dynamics of new media in preventing the spread of misinformation